Sikap pelajar-pelajar terhadap pendidikan AIDS di sekolah - Murukesu, A/L M. Margapandu (1997)
The purpose of this study was to determine students attitude towards AIDS Education in school. This study also investigated the significant differences in attitude among students towards AIDS Educations based on selected demographic factors. The study then, sought to identify the relationship between students' attitude and the following factors: motivation of students, prior knowledge pertaining to AIDS, teachers, parents, culture, peer group and the mass media and then determine the factors most influencing students' attitude towards AIDS Education. The sample chosen for this study consisted of 221 Form four students from five secondary schools in Sandakan, Sabah.